Quantification of ions with identical mass-to-charge (m/z) ratios by velocity-map imaging mass spectrometry. - Bull, J; Lee, J; Vallance, C (Royal Society of Chemistry, 2013)
By integrating a velocity-map imaging lens and position sensitive detector into an electron-impact time-of-flight mass spectrometer, it becomes possible to record ion kinetic energy release (KER) distributions for each fragment ion alongside the time-of-flight mass spectrum. The KER distributions allow ions of identical mass-to-charge ratio to be distinguished and quantified.